Penurunan Risiko Banjir Menggunakan Kolam Takungan Kering - Asmuni, Noredah (Universiti Sains Malaysia, 2006)
Effect of urbanizations on increasing peak discharge and volume of runoff caused serious flood risk impact. Therefore, quantity and quality control of runoff by control at source concept have been implemented. This research studies the effectiveness of Bio-Ecological Drainage System (BIOECODS) that combine the system of infiltration, storage, flow retardation, swale and water treatment as stated in Urban Stormwater Management Manual (MSMA). A study of “Flood Risk Reduction Using Dry Pond” have been completed to study one of BIOECODS component, dry pond as runoff storage and its capability to retain stormwater runoff. The result from this research show that dry ponds application are effective to retain a volume of stormwater runoff, reduce peak flow and reduce flood risk impact. Infiltration test and sieve analysis test were carried out to know the dry pond effectiveness to infiltrate through the soil and reduce the peak flow. From the study it is concluded that the dry ponds are effective to reduce peak flow, detention storage system at certain volume and can be use as an application to reduce the flood risk.